Feminist Analysis of Twinkle Khanna’s Short Story the Legend of Lakshmi Prasad - Javed Iqbal; Shamim Ali (JSSH, 2024)
This paper conducts a socialist feminist analysis of Twinkle Khanna's "The Legend of Lakshmi Prasad." By examining the protagonist's experiences within a patriarchal Indian society, the study explores themes of economic inequality, domestic labor, and the intersectionality of gender and class. Drawing on Zillah R. Eisenstein's theory of feminism, the analysis investigates how Lakshmi Prasad's lack of financial independence and excessive domestic burdens contribute to her marginalized status. A qualitative close-reading approach was employed to analyze the text and its portrayal of gender dynamics. The paper proposes practical solutions, such as promoting women's economic empowerment and challenging traditional gender roles, to address these issues and create a more equitable society. Women in the subcontinent, since 19th century, have been facing a systemic marginalization and domestic abuse due to deep-rooted socio-economic inequalities within a patriarchal society. The Indian English literature, with its rich tradition of exploring social and cultural issues, provides a powerful platform for examining these experiences. This research aims not only to shed light on the ongoing struggles faced by women in a male-dominated society but also to propose practical solutions that could empower them and elevate their social status.